Towards establishing a security engineered SCADA framework. Issue 1 (2nd January 2019) - Hopkins, Stephen; Kalaimannan, Ezhil
ABSTRACT: Today, Supervisory Control and Data Acquisition (SCADA) devices find their use across a wide range of industries. SCADA applications include industrial, infrastructure, facility, and unique private systems. The evolution of SCADA to interconnect multiple remote locations and networks, communicate over Transmission Control Protocol/Internet Protocol (TCP/IP) on Local Area Networks (LAN) connected to the internet, and integrate with Internet of Things (IoT) and other Internet Enabled Devices (IED) extends vulnerability exposure risks to the internet and presents a greater need for security considerations for design, implementation, and use. The research in this paper presents the SCADA vulnerability baseline and examines mitigation through an integrating and encapsulating Framework We present a securely engineered SCADA framework which provides an improvement in security, performance and return of investment for industrial applications.